Quality assessment and authenticity evaluation of honey samples from local traders in Peshawar, Pakistan - Abdul Wahab; Muhammad Younus; Shehla Begum; Wahid Gul (Environmental Monitoring and Assessment, 2026)

Assessment of Growth, Chemical Composition, and Antioxidative Capacity of Coho Salmon (Oncorhynchus kisutch) Alevins Fed Dietary Vitamin A Under Controlled Conditions - Leyong Yu; Hairui Yu; Abdur Rahman; Govindharajan Sattanathan; Han Zhang; Lingyao Li; Shahid Sherzada; Mehnoor Sameer; Muhammad Younus (Fishes, 2025)
Vitamin A (VA) is an essential micronutrient that improves growth, immune activity, and antioxidant responses in fish. This study focuses on optimizing VA dietary levels for Oncorhynchus kisutch (Coho salmon) alevins. A 12-week trial was conducted using seven diets containing graded dietary VA levels of 244, 957, 1902, 3494, 6906, 10,248, and 25,213 IU/kg. A total of 2100 fish were reared in 21 tanks; 100 fish were housed in each tank, and 3 tanks represented one treatment. Peak (SGR) and FBW were observed at 6906 IU/kg. Excess VA levels (>15,000 IU/kg) compromised feed conversion efficacy and led to oxidative stress. Analysis of proximate composition resulted in protein and lipid deposition at optimal VA levels. However, excess may have led to metabolic disturbances and reduced ash content. The activity of the antioxidant enzymes catalase (CA), acid phosphatase (ACP), alkaline phosphatase (AKP), and total superoxide dismutase (T-SOD) revealed biphasic patterns, peaking at 6906 IU/kg and dropping when VA levels were exceeded, inducing pro-oxidant effects. Malondialdehyde (MDA), the indicator of toxicity, had a minimal value of 15,000 IU/kg. VA accumulation in the liver showed a dose-dependent relationship, while excess storage (>25,000 IU/kg) induced hepatotoxicity. Quadratic regression was used to identify the optimum VA levels required in Coho salmon alevins, ranging from 6906 to 10,248 IU/kg. Polynomial quadratic regression results indicated that the predicted dietary inclusion of VA at 3000 IU/kg and 15,000 IU/kg may yield better results of T-SOD and MDA. Real-world experimentation is recommended to explore long-term VA optimization with other nutrients and promote better feed utilization and sustainable aquaculture practices.

Low frequency electrostatic wave dynamics in the subsolar magnetosheath of Venus: A theoretical framework with multi-ion and suprathermal electrons - Adil Murad; Muhammad Adnan; Shahida Parveen; Ikramullah; Fida Younus Khattak (Planetary and Space Science, 2025)

Synergistic Application of Biochar and Bio-Organic Phosphate Enhances Drought Tolerance in Maize by Modulating Antioxidant Defense and Reducing Oxidative Stress - Ghulam Sarwar; Zainab Zahra; Tauseef Anwar; Huma Qureshi; Faizan Khalid; Muhammad Waqar Hassan; Muhammad Younus; Muhammad Sajid-ur-Rehman; Huma Rao; Faisal Shahzad; Wajid Zaman; Mansour Shrahili; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Regulation of energy metabolism by non-coding RNAs in livestock species: a review - Faiz-ul Hassan; Muhammad Safdar; Muhammad Younus; Muhammad Asif Arain (Journal of Comparative Physiology B, 2025)

Chemical profiling and biological activities of Dipterygium glaucum Decne.: An in-vivo, in-vitro and in-silico evaluation - Afia Shahid; Duraiz Ahmed Khan; Hanan Y. Aati; Asmaa E. Sherif; Chitchamai Ovatlarnporn; Musaddique Hussain; Huma Rao; Muhammad Imran Khan; Muhammad Younus; Abdul Basit; Kashif ur Rehman Khan (South African Journal of Botany, 2023)

Genomic-based characterization of Enterococcus spp.: an emerging pathogen isolated from human gut - Zumara Younus; Sagar M. Goyal; Vikash Singh; Aamer Ikram; Muhammad Imran (Molecular Biology Reports, 2021)

Phytochemical profiling, in vitro and in vivo anti-inflammatory, analgesic and antipyretic potential of Sesuvium sesuvioides (Fenzl) Verdc. (Aizoaceae) - M. Sajid-ur-Rehman; Saiqa Ishtiaq; Mohsin Abbas Khan; Meshal Alshamrani; Muhammad Younus; Ghazala Shaheen; Muhammad Abdullah; Ghulam Sarwar; Muhammad Sohaib Khan; Faraza Javed (Inflammopharmacology, 2021)

Comparative effects of dietary micro- and nano-scale chitosan on the growth performance, non-specific immunity, and resistance of silver carp Hypophthalmichthys molitrix against Staphylococcus aureus infection - Naima Younus; Amina Zuberi; Tariq Mahmoood; Wasim Akram; Muhammad Ahmad (Aquaculture International, 2020)

Journey of begomovirus betasatellite molecules: from satellites to indispensable partners - Muhammad Mubin; Sehrish Ijaz; Nazia Nahid; Muhammad Hassan; Ayesha Younus; Javaria Qazi; Muhammad Shah Nawaz-ul-Rehman (Virus Genes, 2020)

Managing plastic waste disposal by assessing consumers’ recycling behavior: the case of a densely populated developing country - Farhana Khan; Waqar Ahmed; Arsalan Najmi; Muhammad Younus (Environmental Science and Pollution Research, 2019)

Seasonality in hospital admissions of Crimean-Congo hemorrhagic fever and its dependence on ambient temperature—empirical evidence from Pakistan - Tariq Abbas; Zhiwei Xu; Muhammad Younus; Abdul Qayyum; Muhammad T. Riaz (International Journal of Biometeorology, 2017)

Serological, molecular detection and potential risk factors associated with camel brucellosis in Pakistan - Sana Fatima; Iahtasham Khan; Amar Nasir; Muhammad Younus; Muhammad Saqib; Falk Melzer; Heinrich Neubauer; Hosny El-Adawy (Tropical Animal Health and Production, 2016)

Haematology and blood chemistry references values for clinically healthy red-wattled lapwing (Vanellus indicus) - Sajid Umar; Kiran Aqil; Rizwan Qayyum; Muhammad Younus; Qamar-un-Nisa; Shahzad Ali; Muhammad Ali Shah; Muhammad Irfan; Muhammad Usman; Asif Ali; Akbar Ali; Adnan Ayan; et al. (European Journal of Wildlife Research, 2016)

Illusions of objectivity and a recommendation for reporting data mining results - Manfred Hauben; Lester Reich; Charles M. Gerrits; Muhammad Younus (European Journal of Clinical Pharmacology, 2007)